Ian Worthington - Borja Antela-Bernárdez (Karanos)
Ian Worthington has been a brilliant voice concerning Ancient Greek History during the last decades. Within his academic production, very diverse in themes, topics and interests, different approaches stand out on Macedonia, Philip and Alexander, side by side with his interest also on the voice of Demosthenes (side by side in Worthington’s work with other orators) or the history of Athens. Born in 1958, this Englishman studied Classics in Hull and Durham. He received the highest title of Curators’s Distinguished Professor of History at the University of Missouri in 2013, among other prominent awards. He has also taught in many different institutions and countries, including University of New England (Australia) and University of Tasmania. Co-editor with Joseph Roisman of the seminal (and to some point, inaugural) Blackwell’s Companion to Ancient Macedonia, he is also editor-in-chief of Brill’s New Jacoby, and, for those who know him personally, a kind, amazing human being (with a great sense of humor!).